The Use of Indigenous Research Methodologies in Counselling: Responsibility, Respect, Relationality, and Reciprocity - Roy, Nicole (First Peoples Child & Family Review, 2022)
The values of “Responsibility, Respect, Relationality and Reciprocity (the 4Rs)” in Indigenous research methodologies inform the core principles of Indigenous kinship systems. This is most often understood as the interconnectedness to land, relatives, animals, and spirits. Despite ongoing systems of oppression, Indigenous kinship values have not only survived but continue to demand a rightful a place within our education, health, justice, and welfare systems. Through critical self-reflective praxis, I explore how the values of “Responsibility, Respect, Relationality and Reciprocity” that guide Indigenous research methodologies (IRM) can disrupt Western based psychotherapies and counselling practices that too often reproduce harm onto Indigenous peoples. The 4Rs upheld in IRM strengthen kinship by centring the values that promote the beauty and intelligence of Indigenous knowledge systems and generations of knowledge holders.